"I Am an Engineer AND": A Mixed Methods Study of Socially Engaged Engineers. Issue 4 (24th October 2015) - Litchfield, Kaitlin; Javernick‐Will, Amy
Abstract Background Socially engaged engineering activities such as community development have grown rapidly in popularity. The engineers who participate in these activities seem more diverse and more broadly interested than the larger population of engineers in the United States. Purpose/Hypothesis This article compares the personal attributes, specifically personality traits and motivations to study engineering, of members of a prominent engineering service organization, Engineers Without Borders (EWB‐USA), with the attributes of engineers who were not members. Design/Method Using an exploratory, sequential mixed methods approach that combined variable‐oriented analysis of interviews and focus groups with multiple logistic regression models from responses to a national survey, we compared engineers' personality traits and motivations to study engineering. Results Results indicate that both EWB‐USA members and nonmembers exhibit strong personality traits for conscientiousness and emotional stability. Both members and nonmembers have similar intrinsic engineering interests and motivations. EWB‐USA members have significantly stronger personality traits for openness to experience and agreeableness, stronger motivations for social good, and broader interests than do nonmembers. Conclusions EWB‐USA members have personal attributes that match those of other engineers, but they have broader interests and motivations than do other engineers. These differences suggest including socially engaged engineering activities in engineering may increase the number and broaden the diversity of engineering students and practitioners.